Teaching excellence and how it is awarded: A Canadian case study - Miller-Young, Janice; Sinclair, Melina; Forgie, Sarah (Canadian Journal of Higher Education, 2020)
Quality teaching and how to assess and award it, continue to be an area of scholarship and debate in higher education. While the literature demonstrates that assessment should be multifaceted, operationalizing this is no easy task. To gain insight into how teaching excellence is defined in Canadian higher education, this empirical study collected and analysed the criteria, evidence, and standards for institutional teaching awards from 89 institutions and 204 award programs across Canada. The majority of awards included criteria such as specific characteristics of teaching performance and student-centredness; while activities that had impact outside an individual’s teaching practice were also prevalent, including campus leadership, scholarship of teaching and learning, and contributions to curriculum. Lists of potential sources of evidence were heavily weighted towards student perceptions and artefacts from instructors’ teaching. Recommendations for individuals and institutions wanting to foster excellence in teaching are offered along with suggestions for future research.